Capital Intensity Effects on International Capital Flows and Current Account of ASEAN+ 6 Countries - Setyari, Ni Putu Wiwin; Kartika, I. Nengah; Wenegama, I. Wayan; Dewi, Ni Putu Martini; Sudiana, I. Ketut (International Journal of Economics and Financial Issues, 2017)
One of the results of the theory of comparative advantage Heckscher-Ohlin-Mundell is the substitution relationship between trades and international capitals. This is due to the absence of incentives for capital to move if a trade has been opened. This paper attempts to examine the effect of a country’s comparative advantage on international capital flows which are reflected in changes in its current account balance. The development of a new theory predicts that a country with high capital intensity will receive larger international capital flows than other countries with lower capital intensity. Using panel data from the member of ASEAN + 6 countries estimation results indicate an increase in capital inflows when a country has relatively higher capital intensity and encourage larger current account deficit. The analysis was applied to dynamic panel models with attention to heterogeneity and endogeneity problems that arise in the use of panel data. Keywords: international capital flows, current account adjustment, open economy macroeconomics, macroeconomic impacts of globalization JEL Classifications: F21, F32, F62